Modeling the indirect effect of Wolbachia on the infection dynamics of horizontally transmitted viruses - Strauß, Jakob F.; Telschow, Arndt (Frontiers in Microbiology, 2015)
Intracellular bacteria of the genus Wolbachia are widely distributed in arthropods. There is growing empirical evidence that Wolbachia directly interacts with viruses and other parasites inside the arthropod host, sometimes resulting in low or no pathogen replication. Previous theoretical studies showed that this direct effect of Wolbachia can result in a reduced virus prevalence (within the population), suggesting that Wolbachia could be used in the biological control of vector-borne diseases (e.g., dengue fever). However, Wolbachia might also indirectly affect virus dynamics because Wolbachia-induced reproductive phenotypes (cytoplasmic incompatibility or male killing) increase the larval mortality of hosts and thus alter the age structure of populations. We investigated this indirect effect using mathematical models with overlapping generations, and found the results to depend strongly on the host's life history. In general, the indirect effect can result in two different outcomes: (1) reduced virus prevalence and virus invasion ability, and (2) increased virus prevalence and virus invasion ability. The former occurs for host species with larval competition and undercompensation, the latter for hosts with either adult competition or larval competition and overcompensation. These findings suggest that the effect of Wolbachia on a specific virus is sensitive to the host's life history. We discuss the results with respect to biocontrol programs using Wolbachia.